DISCRETE PT MICROCRYSTALS FIRSTLY FOUND IN LTI BASALTIC LAVA FLOWS, PARANÁ IGNEOUS PROVINCE, STATE OF PARANÁ, BRAZIL. - Costa, Hérlon da Silva; Licht, Otavio Augusto Boni; Vasconcellos, Eleonora Maria Gouvêa; Ferreira, Francisco José Fonseca (Boletim Paranaense de Geociências, 2024)
Platinum Group Elements (PGE) in basalt flows of the Paraná Igneous Province (the South American portion of the Paraná-Etendeka Igneous Province, one of the largest in the world) have been related in previous studies to a Norils’k-Talnak mineralization model, despite inconsistencies such as the lack of EGP-collecting Ni-sulfides, low levels of S and rare olivine. On the other hand, Licht (2018), Gomes et al. (2018), Lindsay et al. (2021) showed the occurrence of relatively high levels of EGP (up to 18 ppb Pt and 9 ppb Pd) in tholeiitic basalts flows of the geochemical types 1-CN, 2 and 3 (Licht 2018), all belonging to magma-type Paranapanema (Peate et al. 1992) and composing the magnetite and Ti-magnetite-rich Paranapanema Formation (Licht & Arioli 2018). The magnetite-PGM association in PIP had already been proposed by Arioli (2008).